Risk factors of cardiac diseases in faculty members and educational staff - Ghabelgoo, M; Abgineh Esfandiyari, S (Advances in Nursing & Midwifery, 2009)
Background In spite of different studies for identifying risk factors in cardiovascular diseases, mortality rate resulted from them is worrying. It is estimated that by the year 2020, the rate will reach to 75%. At present, such risk factors as urban lifestyle, stress, diabetes, obesity, immobility, smoking, increased lipids, BUN, creatinine, hypertension etc. have been identified and are under investigation. Purpose This cross-sectional study was carried out to determine identified and probably unknown risk factors in the faculty and educational staff of Islamic Azad University in Karaj city. Methods 242 subjects including 81 (33.5%) faculty members and 161 persons (66.5%) from educational staff were randomly selected. A questionnaire in 2 parts and some clinical as well as paraclinical tests were used for data collection. All data were gathered between 8 AM and 12 MD during heavy workload. Results It was revealed that 44% of the faculty and 46% of the staff had marginal body mass index (BMI). In addition, 14% as well as 26% of the subjects had abnormally higher BMI respectively. In both groups, 63% had higher BMI than normal. Waist circumferences of 62% of the faculty and 76% of the staff were 80 cm or more. 65% had normal blood pressure while it was more than 140/80 mm Hg in 22%. However, in 9% of the faculty and 4% of the staff, the pressure was 100/50 mm Hg. 96% and 91% of both groups did not smoke and fell within normal ranges for blood sugar and urine. The amount of urea and creatinine showed a significant difference between the groups (P=0.000, P=0.009). Conclusion Some known risk factors such as blood sugar and lipids were controlled in the groups but some of them have not been identified as risk factors for cardiac diseases, e.g. BMI, waist circumference, urea and creatinine. A significant relationship exists between blood pressure and job stress as well as coping strategies. This denotes that educational authorities and administrators should modify their plans to control stress and risk factors. Keywords: Cardiac risk factors, Stress, Faculty members, Educational staff.